TINDAK UJAR KOMISIF DALAM NOVEL HERZOG KARYA SAUL BELLOW (SUATU ANALISIS PRAGMATIK) - PUA, GABRIELA ANASTASIA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT Â  This reseach entitled Commisive Act in the novel Herzog by Saul Bellow. In pragmatic field, communication is a fission of problem. Leech (1983) devide the speech situation into five aspects one of them is speech act. Speech act is a communication act. Austin (1962) verify the speech act into three categories that are locutionary act, illocutionary act, and perlocutionary act. Austin classifies the utterance according to illocutionary meaning that are verdictives, executives, commisives, behabitives and expositives. Commisives act is a speech act that ask the speaker doing something in the future such as promising. This research attemps to identify, classify, and analyze the commisive act in the novel Herzog by Saul Bellow. The identified data are analyzed according to Austin theory, and in analyzing the data, the writer uses descriptive method. The result of this research show the kinds and function of the commisive act according to Austin. The result of this research show that the kinds of these entire commisive act found in the novel are persuade, offering, engage, plan, bet, agree, persuade, oppose, espouse, guarantee, engage, promise and swear. Offering is the most used function in the novel. Â  Key words : Commisive act, Pragmatic Analysis, Novel â€œHerzogâ€